Non-Collinear Phase in Rare-Earth Iron Garnet Films near the Compensation Temperature - Dmitry A. Suslov; Petr M. Vetoshko; Alexei V. Mashirov; Sergei V. Taskaev; Sergei N. Polulyakh; Vladimir N. Berzhansky; Vladimir G. Shavrov (Crystals, 2023)
The experimental discovery of the suppression effect of the non-collinear phase in strong magnetic fields near the compensation point in ferrimagnetic structures was made. The observations were carried out using the magneto-optical method by creating a lateral temperature gradient in the plane of the epitaxial films of iron garnets. The non-collinear phase is absent in weak magnetic fields. If an external magnetic field exceeds the first critical value, the non-collinear phase arises near the compensation point. The temperature range of the non-collinear phase expands due to the field increase up to the second critical value. Further field increases conversely reduce the temperature range of the non-collinear phase so that the field above the second critical value causes the disappearance of the non-collinear phase. The effect of the occurrence and suppression of the non-collinear phase is demonstrated on samples of two types of iron garnet films with two and three magnetic sublattices. Phase diagrams of the magnetic states in the vicinity of the critical point are constructed, and it is shown that the region of existence of the non-collinear phase in a two-sublattice magnet is smaller than in a three-sublattice one.